Exploring the Challenges of Mobile Phone Utilization for Library Service Delivery: The Librarians’ Perspectives - Qudus Bankole (International Journal of Information Science and Management)
This study explored the challenges of utilizing mobile phones for library service delivery from the perspectives of librarians. With the growing use of mobile devices, libraries increasingly integrate mobile technologies to enhance accessibility and service delivery. However, the implementation faces significant challenges that need to be addressed. The study employed a survey research design with a sample of 143 professional librarians across seven university libraries in North-Central Nigeria. A self-developed questionnaire was used to collect data, which was analyzed using descriptive statistics. The findings revealed that librarians can provide services such as self-help, selective dissemination of information, inter-library loans, current awareness services, library information services (news, opening hours changes, and notices of recent acquisitions), loan services (including book renewals and overdue reminders), making reservations, checking the availability of short-term borrowing items, and Online Public Access Catalogue (OPAC) access. However, several challenges were identified, including limited bandwidth, content ownership, licensing and digital rights management, privacy and security concerns, high costs of service provision, inadequate user education, restrictive library policies on mobile device usage, maintenance issues, and the need for better staff training on technology. The study concluded that addressing these challenges requires a multifaceted approach, including improving infrastructure, developing comprehensive policies, enhancing user education, and investing in staff training among librarians in university libraries in North-Central Nigeria. Recommendations included enhancing network infrastructure, establishing clear digital content policies, implementing robust security measures, developing cost-effective mobile services, providing user and staff education, updating policies to support mobile access, and ensuring routine maintenance and technical support